Connected Vehicles and IoT: A Global Bibliometric Analysis of Intelligent Transport Systems and Communication Protocols - Judijanto, Loso (Westscience Press, 2025)
The convergence of connected vehicles and the Internet of Things (IoT) has significantly transformed the development of intelligent transport systems (ITS), enabling real-time communication, automation, and enhanced mobility solutions. This study conducts a global bibliometric analysis using VOSviewer to map the scientific landscape of this rapidly evolving field, with a specific focus on communication protocols such as vehicle-to-vehicle (V2V), vehicle-to-everything (V2X), and 5G systems. A dataset of 1,132 Scopus-indexed publications (2010–2025) was analyzed to identify key research themes, collaboration networks, and temporal trends. The co-occurrence network reveals a central concentration around intelligent systems, IoT, and vehicular communication, while overlay and density visualizations show a thematic progression toward information management, smart cities, and 5G infrastructure. Co-authorship analysis indicates a cluster of influential researchers, with India emerging as a central hub in international collaborations. Despite robust technological development, gaps remain in policy, governance, and interdisciplinary research. This study offers strategic insights for academics, industry stakeholders, and policymakers aiming to contribute to the sustainable evolution of smart mobility ecosystems.